Tactical Approach with Drilling Method on Shooting Ability of Futsal Extracurricular Participants in Elementary Schools - Hidayat J, Taufik; Hudain, Muh. Adnan; Hasan, Muh. Said; Kasmad, Muhammad Rachmat; Jamaluddin, Jamaluddin (ETDC: Indonesian Journal of Research and Educational Review, 2025)
The background of this study is based on the importance of mastering shooting skills in futsal games, especially at the elementary school level, as well as the need for effective training methods to improve these abilities. This study aims to determine the effect of tactical approaches and drilling methods on the shooting abilities of elementary school futsal extracurricular participants. This study uses a quantitative approach with an experimental method and a two-group pretest-posttest design. The sample in the study amounted to 28 students who actively participate in futsal extracurricular activities at elementary school Parang Tambung II Makassar City. The sampling technique used the total sampling method and then divided into two groups: the tactical approach group and the drilling method group. The research instrument used was a shooting accuracy test from Maulana (2009), which has been tested for validity and reliability. Data analysis was carried out using a t-test with a significance level of 0.05. The results of the study showed that (1) there is a significant influence of the tactical approach on shooting ability (p < 0.05); (2) there is a significant influence of the drilling method on shooting ability (p < 0.05); and (3) there is a significant difference in the influence between the tactical approach and the drilling method on shooting ability (p = 0.002 < 0.05). The group with the tactical approach showed a higher increase in shooting ability than the drilling method group, with an average difference of 3.50 points.